2007
DOI: 10.1063/1.2775430
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic potential fluctuation induced by charge discreteness in a nanoscale trench

Abstract: Plasma molding over deep trenches and the resulting ion and energetic neutral distributionsA simplified two-dimensional Monte Carlo simulation is performed to estimate the charging potential fluctuations caused by strong binary Coulomb interactions between discrete charged particles in nanometer scale trenches. It is found that the discrete charge effect can be an important part of the nanoscale trench research, inducing scattering of ion trajectories in a nanoscale trench by a fluctuating electric field. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Liu et al [9] have studied the field emission of electrons from array of carbon nanotubes. Lee et al [10] have carried out simulations to estimate the charging potential fluctuations caused by strong binary Coulomb interactions between discrete charged particles in nanometer scale trenches. Iheludev and Emel'yanov [11] have studied phase matched second harmonic generation from nanostructure metallic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [9] have studied the field emission of electrons from array of carbon nanotubes. Lee et al [10] have carried out simulations to estimate the charging potential fluctuations caused by strong binary Coulomb interactions between discrete charged particles in nanometer scale trenches. Iheludev and Emel'yanov [11] have studied phase matched second harmonic generation from nanostructure metallic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the notching effects during etching due to charging and the distortion of ion trajectories have been simulated by using Monte Carlo simulation [5∼8] and other methods [9] . LEE et al found that the width of the trench affected the shapes of the IEDs [10] . MADZIWA-NUSSINOV presented a clear result about the ion trajectories in the photoresist trenches [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…The need to remedy these artifacts has been the motive for several theoretical and computational studies on surface charging. The majority of them focus on dielectric, mainly Silicon dioxide Twisting Etching lag (SiO2) trenches or holes [130][131][132][133][134][135][136][137][138][139][140][141], some of them on Si trenches with a dielectric mask [142][143][144] and/or on SOI wafers [120,145,146].…”
Section: Computational Studies On Surface Charging Of Conventional Microstructures In Microelectronicsmentioning
confidence: 99%
“…Kenney and Hwang [137] investigated the stochastic behavior of charging by studying the oscillation of charging potential in high AR dielectric nanostructures. Lee et al [136] surmised that large electrostatic potential fluctuations due to stochastic charging could lead to profile irregularities as the trench size was reduced to nanometer scale. Zhang et al [158][159][160][161] presented a computational research regarding plasma induced surface charging on the top surface of mask holes.…”
Section: Computational Studies On Surface Charging Of Conventional Microstructures In Microelectronicsmentioning
confidence: 99%
See 1 more Smart Citation